The Application of Biomedical Engineering Techniques to the Diagnosis and Management of Tropical Diseases: A Review - Ibrahim, Fatimah; Thio, Tzer Hwai Gilbert; Faisal, Tarig; Neuman, Michael (MDPI AG, Basel, Switzerland, 2015)
This paper reviews a number of biomedical engineering approaches to help aid in the detection and treatment of tropical diseases such as dengue, malaria, cholera, schistosomiasis, lymphatic filariasis, ebola, leprosy, leishmaniasis, and American trypanosomiasis (Chagas). Many different forms of non-invasive approaches such as ultrasound, echocardiography and electrocardiography, bioelectrical impedance, optical detection, simplified and rapid serological tests such as lab-on-chip and micro-/nano-fluidic platforms and medical support systems such as artificial intelligence clinical support systems are discussed. The paper also reviewed the novel clinical diagnosis and management systems using artificial intelligence and bioelectrical impedance techniques for dengue clinical applications.